Preliminary study on microR-148a and microR-10a in dermal papilla cells of Hu sheep - Xiaoyang Lv (BMC Genetics, 2019)
Abstract Background Hu sheep, a unique Chinese breed with high reproductive performance, are also well known for their rare white lambskin in China. The quality of lambskin is affected by hair follicles, and dermal papilla cells are an important component of hair follicles that plays a key role in hair follicle growth and development. This study helps elucidate the effect of miR-148a and miR-10a on hair follicle growth and development. Results Based on the results of gene chip and high-throughput sequencing, bone morphogenetic protein 7 (BMP7) was used as a research object. Bioinformatics analysis and the dual-luciferase reporter system indicated that, along with Western blot and quantitative real-time polymerase chain reaction (qRT-PCR) that miR-148a and miR-10a target relationships with BMP7. BMP7 was the target gene both for miR-148a and miR-10a by the dual-luciferase reporter system and Western blot. Hu sheep dermal papilla cells were successfully isolated and purified, and after transfecting miR-148a/miR-10a mimics and inhibitors into dermal papilla cells, a Cell Counting Kit-8 (CCK-8) was used to determine that miR-148a/miR-10a inhibited the proliferation of Hu sheep dermal papilla cells. In addition, after the overexpression of miR-148a, the expression levels of Smad3 (P < 0.05), Smad6 (P < 0.05), Smad4 (P < 0.01), and Smad5 (P < 0.01) were significantly higher than those of the control groups. After the inhibition of miR-148a, the expression levels of Smad3 (P < 0.05), Smad4 (P < 0.05), and TGF-β (P < 0.01) were significantly lower than those of the control groups. After the overexpression of miR-10a, the expression levels of Smad1 (P < 0.01), Smad2 (P < 0.05), Smad4 (P < 0.01), Smad5 (P < 0.01), and TGF-β (P < 0.05) were significantly lower than those of the control groups. After the inhibition of miR-10a, the expression levels of Smad1 (P < 0.01) and Smad2 (P < 0.05) were significantly lower than those of the control groups. Conclusions These results revealed the target relationship between miR-148a, miR-10a and BMP7, and the effect of miR-148a and miR-10a on the proliferation of dermal papilla cells. They will provide the basis for a follow-up study on how miR-148a, and miR-10a mediate BMP7 regulation of hair follicle growth and development.